IOT Enabled Health MonitoringSystem for Infants - Mansi Swami, Koena Biswas, Ms. K. Meenakshi, Aditya Sharma, AbhyudayaPurwar (International Journal of Advanced Science and Technology, 2020)
Healthcare is one of the prime concerns of Indian population and with Infant Mortality Rate at 33 infant deaths per thousand live births in 2017 there is a need for multi-functional IOT (Internet Of Things) systems to monitor the vitals of patients. Wepresent a system that logs and analyzes real-time temperature, pulse and heartbeat data to predict possible health conditions of an infant. The system also aims at monitoring the air quality of the surroundings to ensure a non-toxic environment for theinfants. Our system consists of multiple sensors that map the real-time readings to the micro controller which then sends them via a Wi-Fi module to the cloud. This data is used to predict any extreme health conditions which results in fatalities among newly born infants. We have also incorporated a Machine Learning module which uses Image Classification for jaundice detection. Our focus in this research work is to predict common health conditions in infants like jaundice, pneumonia and high fever which are common causes of death ininfants.